LEAD ACID BATTERY MODELING FOR ELECTRIC CAR POWER SOURCES - Bambang Sri Kaloko (Universitas Gadjah Mada, 2009)
Successful commercialization of electric vehicles will require a confluence of technology, market, economic, and political factors that transform EVs into an attractive choice for consumers. The characteristics of the traction battery will play a critical role in this transformation. The relationship between battery characteristics such as power, capacity and efficiency, and EV customer satisfaction are discussed based on real world experience. A general problem, however, is that electrical energy can hardly be stored. In general, the storage of electrical energy requires its conversion into another form of energy. Electrical energy is typically obtained through conversion of chemical energy stored in devices such as batteries. In batteries the energy of chemical compounds acts as storage medium, and during discharge, a chemical process occurs that generates energy which can be drawn from the battery in form of an electric current at a certain voltage. A computer simulation is developed to examine overall battery design with the MATLAB/Simulink. Battery modelling with this program have error level less than 5%.